Evaluation of the phytoestrogenic activity of honeybush (Cyclopia) - Verhoog, Nicolette Jeanette Dorothy (Stellenbosch : University of Stellenbosch, 2006)
Thesis (MSc (Biochemistry))--University of Stellenbosch, 2006.